2014
DOI: 10.1097/scs.0000000000001000
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Role of Magnetic Resonance Imaging in Assessing Orofacial Pain and Paresthesia

Abstract: The aim of this study was to compare the efficacy of CT and MRI in evaluating orofacial pain and paresthesia. A total of 96 patients with orofacial pain and/or paresthesia were included in this study. The patients who underwent CT and/or MRI examinations were assessed, and the efficacy of CT and/or MRI examinations in detecting the causative disease of the orofacial pain and paresthesia was evaluated. Seventy (72.9%) of 96 patients underwent CT and/or MRI examinations. Whereas CT examinations detected 2 diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Despite such findings, currently, there is no evidence of the request for MRI in patients with COFP. Structural MRI is a common screening tool used by clinicians in the differential diagnosis of several types of COFP in order to exclude structural lesions, such as intracranial tumors and cysts, or any vascular compression of the trigeminal nerve ( Ohba et al, 2014 ; Devine et al, 2019 ). In a recent study of Devine et al (2019) on 125 patients with different types of COFP, except BMS, the authors found no alteration in the MRI scan in 51.2% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Despite such findings, currently, there is no evidence of the request for MRI in patients with COFP. Structural MRI is a common screening tool used by clinicians in the differential diagnosis of several types of COFP in order to exclude structural lesions, such as intracranial tumors and cysts, or any vascular compression of the trigeminal nerve ( Ohba et al, 2014 ; Devine et al, 2019 ). In a recent study of Devine et al (2019) on 125 patients with different types of COFP, except BMS, the authors found no alteration in the MRI scan in 51.2% of patients.…”
Section: Discussionmentioning
confidence: 99%